Characterization of smallholder poultry production and marketing system of Dale, Wonsho and Loka Abaya Weredas of Southern Ethiopia - Gebre-Egziabher, M.M. (Hawassa University, 2007)
A longitudinal data collection (repeated survey) and a cross sectional survey was conducted in three weredas of southern Ethiopia to characterize the smallholder poultry production and marketing systems there by to identify the major constraints and priorities for poultry improvement and extension interventions. A structured questionnaire and Participatory Rural Appraisal (PRA) methods relevant to rural poultry production were used to collect data. Using a stratified random sampling technique, hundred and sixty households were included in the survey. The result showed that the main objectives of chicken production in the study area were for sale (44%), replacement (34%) and consumption (22%) and that of eggs used for hatching (47%), sale (33 %) and home consumption (20 %). The most dominant chicken production system in the study area was a subsistence extensive system which is based on indigenous chickens with scavenging and seasonal supplementary feeding of homegrown grains and household food refusals. The overall mean flock size for the three weredas was 9.22±0.35 with a range of 3 -26. Nearly all (97.6 %) of the respondents do not have a separate house to their chickens and only 10% of the respondents have access to veterinary services. Poultry production was managed based on indigenous or local knowledge they have acquired over their lifetime. The high hatchability (89.1 %) and mortality (80%) are the two conflicting feature of the system. Men and women took 35 % and 24.4% ownership respectively. The major decision role belongs to men. However, the major management was the responsibility of women. The overall average age at first egg was 7.07±0.08 ranging 5-10 months. The average egg production per clutch was 14.9±0.23 ranging (6-26) with a mean 3.7±0.04 clutches per year ranging 2-5 clutches with a clutch length of 26.2±0.41 days. The overall mean cock: hen ratio was 1:2.2. Chickens in Wonsho (Dega) wereda showed significantly (p<0.05) best performance with the highest egg production (62.95 eggs/hen/year), lowest chick mortality (45.15) and highest clutches per year (3.8) compared to other Weredas. The mean live-weights for matured male and female at farm Gate were 1.58±.02 (kg) and 1.30±.02 (kg), respectively. The corresponding price for matured male and female at farm gate were 21.74±0.54 and 13.95±0.43 birr, respectively in during ordinary days. More than half of the respondents (65%) do not have any information about the price of the chicken. Only 31.67% of the volumes of sale pass directly to the consumer. Critical constraints of the smallholder poultry production in the study area were partly due to the prevailing poor management practices, in particular predation, lack of proper health care, and poor housing. It was concluded that efforts have to be made to shift the production paradigm to semi intensive focusing on market oriented production based on scavenging with a holistic support of services such as health, housing, extension, credit and marketing to make it productive and sustainable.